If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 2) + 15n = 114 Reorder the terms: 3(2 + n) + 15n = 114 (2 * 3 + n * 3) + 15n = 114 (6 + 3n) + 15n = 114 Combine like terms: 3n + 15n = 18n 6 + 18n = 114 Solving 6 + 18n = 114 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 18n = 114 + -6 Combine like terms: 6 + -6 = 0 0 + 18n = 114 + -6 18n = 114 + -6 Combine like terms: 114 + -6 = 108 18n = 108 Divide each side by '18'. n = 6 Simplifying n = 6
| 7x=7(x-2) | | 6x-8=70 | | 6x=2(5x+12) | | 0.75x=-15 | | 9a-3(a-6)=66 | | -25+8t+6m-4t-4m+29= | | 15*36= | | -6(6x+6)= | | (x+6)3=33 | | 2x/4+2=6 | | 15.36= | | 8*3x+1=128 | | -5y=20 -10x | | 4d-22=48 | | z-.66=.125 | | 10x-5y=20 | | 2-2=12x+7x | | 2x--3=15 | | 15ax-y+3ay-5x= | | 4(2x-1)+12=2(6-3x) | | -12+3x=42 | | 13x+24=5x-8 | | n+2(n-2)= | | .7(5x+10)=1.5-(x+2) | | 3x+2(x+24)=-7 | | 4(x-1)=4x-8 | | 40x^6y^6-45x^4y^6-5x^4y^5= | | -x/3+2=7 | | -5=-24x | | 14x-0.5=8.9 | | 3(-3x+2)+5(-2x+9)= | | 5b=2 |